2020
DOI: 10.1101/2020.05.24.111997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Choanoflagellates and the ancestry of neurosecretory vesicles

Abstract: Neurosecretory vesicles are highly specialized trafficking organelles important for metazoan cell-cell signalling. Despite the high anatomical and functional diversity of neurons in metazoans, the protein composition of neurosecretory vesicles in bilaterians appears to be similar. This similarity points towards a common evolutionary origin. Moreover, many key neurosecretory vesicle proteins predate the origin of the first neurons and some even the origin of the first animals (metazoans). However, little is kno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Among the highest expressed transcripts in cells of the SNN (C33 metacell) are the putative neuropeptides. Additionally, C33 expresses important components of the bilaterian neurosecretory vesicle pathway, [35][36][37][38] like secretagogin/calbindin, ferlins, synaptotagmin 7, Munc18 (STXBP1), Munc13 (UNC13B), complexin, and neurosecretory SNARE proteins syntaxin 1, VAMP2, 3 and SNAP-25 (Data S2C). 35 homologs of voltage-gated potassium channels, 40 two voltage-gated sodium channels, 41 and the voltage-gated calcium channel MleCav2, 42 as well as several homologs of ionotropic glutamate receptors 15,39 and other ion channels, Na/Ca exchanger, a sodium/potassium transporting ATPase, and two innexins are either overexpressed or detectable in the C33 metacell (Table 1; Data S2D).…”
Section: Newly Identified Putative Neuropeptides Affect Ctenophore Swimming Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Among the highest expressed transcripts in cells of the SNN (C33 metacell) are the putative neuropeptides. Additionally, C33 expresses important components of the bilaterian neurosecretory vesicle pathway, [35][36][37][38] like secretagogin/calbindin, ferlins, synaptotagmin 7, Munc18 (STXBP1), Munc13 (UNC13B), complexin, and neurosecretory SNARE proteins syntaxin 1, VAMP2, 3 and SNAP-25 (Data S2C). 35 homologs of voltage-gated potassium channels, 40 two voltage-gated sodium channels, 41 and the voltage-gated calcium channel MleCav2, 42 as well as several homologs of ionotropic glutamate receptors 15,39 and other ion channels, Na/Ca exchanger, a sodium/potassium transporting ATPase, and two innexins are either overexpressed or detectable in the C33 metacell (Table 1; Data S2D).…”
Section: Newly Identified Putative Neuropeptides Affect Ctenophore Swimming Behaviormentioning
confidence: 99%
“…Recently, it was shown that many components of the synaptic tool kit were present in the last common ancestor of animals (Metazoa) and unicellular choanoflagellates. 3,4 Traditionally, it is thought that the metazoan last common ancestor lacked specialized neuronal cell types and a nervous system, 5 a condition present in extant sponges and Placozoans. 6 Later, a first net-like nervous system evolved as present in cnidarians and ctenophores followed by an increased condensation and diversification in the bilaterian lineage.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a phoenixin peptide in choanoflagellates demonstrates that some animal neuropeptides have pre-metazoan origin and predate nervous systems. Many other neuronal molecules, including neurosecretory components (Göhde et al 2021), postsynaptic proteins (Burkhardt et al 2014), and voltage-gated channel subunits (Moran and Zakon 2014) have a similar history (Burkhardt and Jékely 2021). What could be the functions of NUCB and phoenixin in choanoflagellates and non-neuronal sponges?…”
Section: Discussionmentioning
confidence: 99%
“…This has been proposed as one of the most important pre‐requisites for the evolution of metazoan multicellularity by zoologists such as, Zakhvatkin (1949), and Mikhailov et al (2009). Additionally, some choanoflagellates have been shown to be capable of sexual recombination (Woznica et al, 2017) and express many proteins previously thought to be restricted to specialized metazoan cell types such as neurons (Burkhardt et al, 2011; Göhde et al, 2020). Collective cellular contraction, another feature crucial for Haeckel's invaginatory Gastraea hypothesis and gastrulation, in general, has previously also only been described in Metazoan taxa.…”
Section: The Biogenetic Law and The Gastraea Theory In Later Textsmentioning
confidence: 99%